Optimising the fear of missing out phenomenon as a framework to boost musical concert sales - Supina, Supina; Lautama, Sidharta Sebastiandi (International Journal of Applied Sciences in Tourism and Events, 2024)
The Meetings, Incentives, Conferences, and Exhibitions (MICE) industry, particularly within the domain of music concerts, stands poised for significant enhancement in Indonesia. It is worth noting that Indonesia has successfully hosted numerous international music concerts; however, there is still considerable room for growth compared to other ASEAN countries. This study employs theory synthesis to achieve conceptual integration as a research framework construct by combining the FoMO phenomenon, which is currently prevalent due to the rise of social networking sites (SNS), with different policies facilitating music concerts in Indonesia. This review study aims to achieve its research objectives and establish that the Fear of Missing Out (FoMO) phenomenon can significantly enhance music performance ticket sales. This is achieved by constructing the FoMO trait and the Bergen Facebook Addiction Scale, then classifying products according to each concert theme, whether virtual or physical. By capitalizing on the ubiquitous presence of social networking sites (SNS) and the heightened Fear of Missing Out (FoMO) phenomenon post-COVID-19, we anticipate significant improvements. This conceptual study can serve as a valuable resource for enhancing research on the optimization of music concerts, which is also an area that is still underexplored, particularly in Indonesia.